2017
DOI: 10.4103/0259-1162.186619
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of the effect of intravenous paracetamol and tramadol in relieving of postoperative pain after general anesthesia in nephrectomy patients

Abstract: Aim:The aim of this study was to compare the effect of intravenous paracetamol and tramadol in relieving of postoperative pain after general anesthesia for nephrectomy in prospective donor patients for kidney transplantation.Materials and Methods:A randomized study was conducted on 100 adult patients scheduled for nephrectomy aged from 35 to 55 years of both sexes and divided into two groups and were administered intravenous paracetamol and tramadol for postoperative pain relief and assessed with visual analog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 15 publications
3
6
0
Order By: Relevance
“…Pain scores significantly decreased only after 60 min, and this was observed up to 6 h and pain scores increased thereafter. 17 In our study, we also observed lower VAS scores in tramadol group compared to paracetamol group in the immediate postoperative period and need of rescue analgesics which was higher in paracetamol group in the immediate postoperative period. Post anaesthetic shivering is a common complication that occurs in up to 60% of patients recovering from general anaesthesia.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Pain scores significantly decreased only after 60 min, and this was observed up to 6 h and pain scores increased thereafter. 17 In our study, we also observed lower VAS scores in tramadol group compared to paracetamol group in the immediate postoperative period and need of rescue analgesics which was higher in paracetamol group in the immediate postoperative period. Post anaesthetic shivering is a common complication that occurs in up to 60% of patients recovering from general anaesthesia.…”
Section: Discussionsupporting
confidence: 70%
“…In one of the studies, it was observed that drowsiness was found to be higher in tramadol group. 17 In our study, we observed that agitation was more common in paracetamol group and sedation was more common in tramadol group.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…The severity of pain ranging from moderate to severe in acute post-operative patients is 15-60%. 7 Different trials have compared narcotic analgesics, nonsteroidal anti-inflammatory drug (NSAID), and neuro axial drugs and blocks. 8 For acute postsurgical pain management after major surgeries, narcotic analgesics are most commonly used.…”
Section: Discussionmentioning
confidence: 99%
“…40 In a second randomized study of 100 patients comparing IV acetaminophen to tramadol, tramadol was found to be superior in terms of pain control after nephrectomy. 41 Thus, routine use of IV acetaminophen is not warranted in renal surgery until more data become available.…”
Section: Renal Surgerymentioning
confidence: 99%